Anterior mediastinal tracheostomy – a salvage procedure for tracheal necrosis after thyroidectomy for medullary thyroid cancer: a case-report - Hanan Hemead; Akshay J. Patel; Hannah Jesani; Sajith Kumar; Irfan Ahmed; Sat Parmar; Robert Warner; Neil Sharma; Maninder S. Kalkat (World Journal of Surgical Oncology)
Abstract A 34-year-old male patient with recently diagnosed with medullary thyroid carcinoma underwent total thyroidectomy and radical neck dissection, requiring sharp dissection to separate the tumour from the trachea. He required post operative intubation due to bilateral vocal cord paralysis. He developed ischaemic necrosis of the upper two thirds of the trachea presenting with marked surgical emphysema and an infective wound. The wound was opened, drained and an endotracheal tube was negotiated through the sloughed trachea into the distal intrathoracic trachea with the cuff inflated just above the carina. This complication was managed with total pharyngo-laryngectomy, anterior deep mediastinal tracheostomy and construction of a neo-cervical oesophagus with a free lateral thigh fascio-cutaneous flap. This case highlights the potential complications of a procedure, perseverance, collaboration amongst various disciplines and teamwork for treating a rare and complex condition. The patient was discharged and has had an excellent recovery with good quality of life over two years of follow up.